2022
DOI: 10.3390/children9071029
|View full text |Cite
|
Sign up to set email alerts
|

Art Therapy Open Studio and Teen Identity Development: Helping Adolescents Recover from Mental Health Conditions

Abstract: Adolescent identity development is driven to a significant degree by peer interaction. However, when mental health conditions (MHC) or other crises separate teens from their peers, their identity development can be slowed or arrested. We developed a unique open studio intervention (OS-ID) that could facilitate identity development in teens recovering from MHC, and incorporated this intervention into a therapeutic day school catering to our target population. We utilized qualitative case study research to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A recent systematic review of art therapy studies in youth mental health, which noted the small number of randomized controlled trials and lack of replication studies, reported that the extant literature has provided the strongest evidence for the benefit for youth who have experienced trauma (Braito et al, 2022). Less work has been done on participatory arts interventions, but initial findings from small studies suggest that these kinds of interventions can facilitate empowerment and social support (Gittings et al, 2022) and positive changes in identity development (Kelemen & Shamri-Zeevi, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of art therapy studies in youth mental health, which noted the small number of randomized controlled trials and lack of replication studies, reported that the extant literature has provided the strongest evidence for the benefit for youth who have experienced trauma (Braito et al, 2022). Less work has been done on participatory arts interventions, but initial findings from small studies suggest that these kinds of interventions can facilitate empowerment and social support (Gittings et al, 2022) and positive changes in identity development (Kelemen & Shamri-Zeevi, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cancer patients generally have a low level of self-acceptance ( Li et al, 2010 ). Self-acceptance means that an individual can objectively accept and view himself, establish self-value based on self-recognition, respect and appreciate himself ( Huang et al, 2021 ; Kelemen and Shamri-Zeevi, 2022 ). Adolescent cancer patients are more likely to doubt their own worth and lower their level of self-acceptance ( Lewandowska et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety disorders are characterized by symptoms of anxiety, fear, nervousness, and worry, as well as physical symptoms such as palpitations, shortness of breath, dizziness, and muscle tension ( Birmaher et al, 1997 ; Lewandowska et al, 2021 ). Self-acceptance means that an individual can objectively accept and view himself, establish self-value based on self-recognition, respect and appreciate himself ( Huang et al, 2021 ; Kelemen and Shamri-Zeevi, 2022 ). People with low self-acceptance develop psychological and behavioral problems such as low self-esteem and social withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the evolving understanding of mental health, there has been a significant shift in terminology at a global level. Recently, the United Nations Human Rights Council replaced the term ‘mental illness’ with ‘mental health conditions’ (MHC) [ 77 ]. This new terminology represents a transition from a medical approach to one focused on well-being and a shift in emphasis from pathology to recovery [ 78 ].…”
Section: Introductionmentioning
confidence: 99%